Lebanon's electricity from fuel to solar energy production. (November 2020) - Julian, Maya; Bassil, Nathalie; Dellagi, Sofiene
Abstract: Since 1924, Lebanon planned to use renewable energy and in particular hydraulic energy to produce the national need of electricity. Until the beginning of the 70, many steps have been achieved by the government where in 1974 around 41.5% of the Lebanese electricity was produced from hydroelectric stations. Unfortunately since then and due to the instability in the political regimen, electric plants and networks suffered from destruction, aging, increased demand, hacking and many other deterioration factors. Therefore and based on all the last mentioned troubles the electric sector in Lebanon transformed to be the major economic and environmental problem. This paper aims at presenting and analyzing the actual state of the electric sector in Lebanon emphasizing on its impact on air pollution and on the development of factories and small enterprises. Therefore, it will be shown that the problem with the electrical sector is essentially due to the old networks easily hacked, strong reliance on fuel-based electricity, which leads to increased air pollution without meeting the energy consumption demand. This underproduction of electrical energy leads to the development of a parallel electrical private sector also based on fuel burning what worsened air pollution problems despite all the measures taken by the governments to switch to greener electricity production. A case study on electricity consumption in different locations in Beirut is also presented and used to prove that shifting from fuel to solar production will decrease the economic impact of electricity. Hydroelectric energy was not considered due to a decrease in the precipitation level that made it difficult to produce enough energy from rivers and due to the high cost of rehabilitation and upgrading.